Breast cancer. From molecular biology to personified therapy. - Bondarenko, I. N.; Elhajj, Mohammad H.; Prokhach, A. V.; Zavizion, V. F.; Chebanov, K. O. (Морфологія / Morphologia / Morfologìâ, 2016)
Advances in molecular biology had changed approaches to systemic treatment of breast cancer. Clinical decisions on the choice of optimal treatment regimens are performing on the basis of immunohistochemical and molecular genetic classifications. Their increasing uses have contributed changes of paradigm for cancer treatment - from the empirical to the individualized and personalized. The basis for such approaches is knowledge of molecular epidemiology, heterogeneity of expression of molecular subtypes, prognostic and predictive biomarkers of breast cancer. Breast cancer is a widely heterogeneous disease with 20 histological types, 8, molecular-genetic, 6 genomic subtypes, which are characterized by specific molecular and biochemical properties, different clinical course and different outcomes. Molecular genetic classification, created not on the basis of clinical, anatomical and morphological heterogeneity of tumor cells, and on the basis of their molecular-genetic heterogeneity is widely used in clinical practice. This allowed to separate the patients with breast cancer to molecular 4 subtypes - luminal A, luminal B, HER / 2 positive and triple-negative. The significant role of immunohistochemical tissue tumor markers, estrogen and progesterone receptors, HER / 2-neu, Ki-67, p53 for selection the optimal treatment strategy is analyzing in this review. To increase the effectiveness of breast cancer treatment is possible, using a differentiated and personalized approach based on new molecular genetic classification of breast cancer (gene profiling) or to its analogue - expression classification of breast cancer, based on the principle of diversity of immunohistochemical tumor tissue. Personification of cancer treatment involves a therapy based on the study of individual characteristics of tissue is not only the primary tumor but also its metastases.